HUBUNGAN POLA ASUH ORANGTUA TERHADAP KEMANDIRIAN KEBERSIHAN DIRI (PERSONAL HYGIENE) ANAK AUTIS DI SLB - SILFIA, MADYA; ARDIANINGSIH, FEBRITA (Jurnal Pendidikan Khusus, 2018)
THE RELATIONSHIP OF PARENTING PARENTS OF CHILDREN WITH AUTISM ABOUT INDEPENDENCE OF PERSONAL HYGIENE ACTIVITIES IN SLB HARMONI GEDANGAN SIDOARJO. Name : Madya Silfia NIM : 14010044061 Department : S1- Special Education Faculty : Faculty of Science Education Institution Name : State University of Surabaya Advisor : Dr. Febrita Ardianingsih, M.Sc. Independence of personal hygiene is an ability to conduct personal hygiene activities without help from others. Personal hygiene activities are the basis of cleanliness, beauty, and are the first steps towards a healthy life. This ability is very important for all people, especially for children with autism. This study aims to determine the relationship of parenting parents to the independence of personal hygiene of children with autism in SLB Harmoni Gedangan Sidoarjo. This study uses a qualitative approach with descriptive research types. The research subjects in this study were children with autism aged 6-12 years with elementary school education (SD) at SLB Harmoni Gedangan Sidoarjo with a total of 6 children with autism who had limited personal hygiene abilities. Data analysis techniques in this study using source triangulation and also method triangulation. The results showed that there was a relationship between parenting parents with the independence of personal hygiene of children with autism. The findings in the field showed that children with autism in this research subject who had limited personal hygiene independence had authoritative parenting. Keywords: children with autism, parenting parents, personal hygiene.